Analisis Implementasi Program Klinik Literasi GEDEBUK dalam Meningkatkan Kemampuan Literasi Siswa pada Kurikulum Merdeka - Fitriani, Anita; Attalina, Syailin Nichla Choirin (Lembaga Sosial Rumah Indonesia, 2024)
Purpose – This research aims to identify student literacy problems at SDN 4 Kedungcino and analyze the implementation of the GEDEBUK literacy clinic program.Method – This study used descriptive qualitative method. An approach that aims to describe subjects related to the conditions observed and data collection techniques in this research through the process of observation, interviews and documentation. This research was conducted at SDN 4 Kedungcino. Checking the validity of data from observations, interviews and documentation uses triangulation, where the collected data is analyzed through data reduction, data presentation and drawing conclusions.Findings – The research results show that after the implementation of the GEDEBUK literacy clinic program, students' literacy skills have improved. The impact of implementing this program is that students who previously still had difficulty reading are now starting to be able to read books independently fluently, then students who are still in the reading comprehension stage are now able to tell stories well according to the understanding of the books they read. The existence of this literacy program also makes the school library active again. Research Implications – The research provides important insights for improving literacy in elementary schools. However, further improvements need to be made regarding adequate literacy facilities so that the literacy program can be implemented well and optimally.